The Development of Virtue Using Visual Tales for the Early Childhood, Nong Sarai Subdistrict Administration Organization, Don Chedi District, Suphanburi Province - Kaeokhieo , Kanyakorn; boonputtikorn, chayarat; Chuenboon, Athcha (Saengtham College Journal, 2024)
The objectives of this study were 1) to develop the virtue using visual tales for the early childhood, and 2) to compare virtual before and after using visual tales for the early childhood. The target group used in the research was 17 children in Kindergarten 1, Semester 1, Academic Year 2023, Ban Tha Kum Child Development Center, Nong Sarai Subdistrict Administration Organization, Don Chedi District, Suphan Buri Province. The research tools are 1) tales to promote virtue for early childhood children. Kindergarten 1 Dream Forest. 2) Observation of moral behavior for early childhood in 8 aspects: honesty, patience compassion for others conscience, duty, perseverance, punctuality and acceptance of the consequences of actions, and 3) Moral assessment for Early Childhood. Statistics used to analyze data include mean, standard deviation, and hypothesis test using t-test. The findings revealed that 1) After the virtue using visual tales for all the early childhood were very good level, and 100 percentage all eight aspects: honesty, patience compassion for others conscience, duty, perseverance, punctuality and acceptance of the consequences of actions, and 2) The posttest mean scores using visual tales for the early childhood was found significantly higher than the pretest mean using visual tales for the early childhood.